An Analysis into India’s and China’s Revealed Comparative Advantage on Travel and Tourism Economic and Environmental Impact - MEHDI, Syed Asghar; ASGHAR, Syed Taha (Journal of Environmental Management and Tourism, 2025)
: Travel and Tourism is a major economic sector globally, and countries invest significantly to leverage their natural, cultural, and infrastructural assets. It has come to stay as the largest service industry and widely used as an instrument of growth of national income, poverty alleviation, infrastructure development and employment generation. The Asia Pacific region is slated to be the most preferred tourism regions of world; whereas India, and China, by their size both in terms of geography and population are the rising nations on the global tourism front. As per the different World Travel and Tourism Council reports, these two countries are projected to upsurge in their respective tourism economies both in terms of contribution to GDP and employment in the post pandemic world. However, the growing Economic Impact of tourism also increases the threat of rising Greenhouse Gas (GHG) Emissions impact. The Travel and Tourism Economic and Greenhouse Gas (GHG) Emissions impact cannot be studied in isolation but has to be analyzed for overall advantages for an economy, more so for the massive economies of India and China. This is comprehensive comparative study on the background of bi-decadal economic impact analysis (1995–2015), covering the period prior to the Covid-19 pandemic in India and China leading to study of economic and Greenhouse Gas (GHG) Emissions impact in the pandemic and post pandemic period through the Revealed Comparative Advantage (RCA) Analysis. It aims to assess the potential of tourism as a key driver of sustained and enhanced economic growth as well as focus on control environmental impact in India and China in the coming decades.